Depressive Symptoms among Adolescents in Kuching, Malaysia: prevalence and associated factors - Ang, Ai Ling; Suzaily, Wahab; Helmy, Hazmi; Fairuz Nazri, Abd Rahman; Rosliwati, Md Yusoff (Japan Pediatric Society, 2018)
Background The trend of depression is rising worldwide. There are limited studies on depression among adolescents. This study aimed to estimate the prevalence and identify the factors associated with depressive symptoms among adolescents in Kuching, Malaysia, and to analyze the relationship between depressive symptoms and suicidal ideation. Methods A cross‐sectional study was conducted on 320 students from urban and rural secondary schools. The participants were randomly selected via multi‐stage sampling. They completed the Malay version of Children's Depression Inventory (CDI) and Beck Scale for Suicidal Ideation (BSS). Results The prevalence of depressive symptoms in this study is 26.2%. Binary logistic regression analysis showed that variables with significant association with depressive symptoms were race (p=0.028), type of class (p<0.001), mother's education level (p=0.036), type of housing (p=0.036), parents’ marital status (p=0.012), alcohol intake (p=0.005), stealing (p<0.001) and history of disciplinary record (p=0.005). Variables that remain significant with multivariable logistic regression were type of class (p=0.004), parents’ marital status (p=0.017) and stealing (p<0.001). Students from Arts stream (OR=2.43) with parents who were separated, divorced or widowed (OR=3.13) and had experience of stealing (OR=3.27) were predicted to be at risk to develop depressive symptoms. There was significant correlation between total CDI score and total BSS score (p<0.001). Conclusions The prevalence of depressive symptoms among adolescents in this study is high.Depressive symptoms are significantly correlated with suicidal ideation. Greater collaboration between the education and health agencies is essential for mental health promotion in schools and early detection of depression especially among at‐risk adolescents. This article is protected by copyright. All rights reserved.